PEMBANGUNAN EKONOMI ISLAM DENGAN PENGEMBANGAN KOPERASI SYARI’AH - TESTRU HENDRA (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Cooperative as one business entity that has evolved over 68 years in 2015. The foundation of cooperation and togetherness that is contained in the cooperative to manage economic resources is a tool for people who are not able to escape from poverty, it is in line with expectations as Bung Hatta the father of the cooperative. Cooperative as a pillar is a manifestation of economic democracy as outlined in Article 33 of the Constitution, 1945. It can be seen from a different mechanism of capitalist economic system that promotes individual interests and personal gain alone. However during the course of the cooperative operates based on the system of interest, but the interest drawn by the cooperative finally returned to members as Time Results of Operations (SHU), so that the loans extended by the cooperative to members can be utilized. Nevertheless the interest rate offered is lower than the cooperative banking interest. The basic problem is the system of interest that should not be practiced by MUI Fatwa September 2003, because of riba. Therefore how should the cooperative development of sharia? Islamic products is how to offer, so that cooperatives can help the economy of the middle to lower. Related to the issue of this paper discusses the development of sharia-based cooperatives.